Managing Complex, High Risk Projects A Guide to Basic and Advanced Project Management - Marle, Franck; Vidal, Ludovic-Alexandre (Springer London : Imprint: Springer, 2016)
Maximizing reader insights into project management and handling complexity-driven risks, this book explores propagation effects, non-linear consequences, loops, and the emergence of positive properties that may occur over the course of a project. This book presents an introduction to project management and analysis of traditional project management approaches and their limits regarding complexity. It also includes overviews of recent research works about project complexity modelling and management as well as project complexity-driven issues. Moreover, the authors propose their own new approaches, new methodologies and new tools which may be used by project managers and/or researchers and/or students in the management of their projects. These new elements include project complexity definitions and frameworks, multi-criteria approaches for project complexity measurement, advanced methodologies for project management (propagation studies to anticipate potential behaviour of the project, and clustering approaches to improve coordination between project actors) and industrial case studies (automotive industry, civil engineering, railroad industry, performing arts,...) and exercises (with their solutions) which will allow readers to improve and strengthen their knowledge and skills in the management of complex and (thus) risky projects.